2006
DOI: 10.1124/jpet.106.114769
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Optimized Delivery, Inhibition of Oxidative Stress, and Antiapoptotic Activity of Targeted Nitroxides

Abstract: Suppression of mitochondrial production of reactive oxygen species is a promising strategy against intrinsic apoptosis typical of degenerative diseases. Stable nitroxide radicals such as 4-hydroxy-2,2,6,6-tetramethyl piperidine-1-oxyl (TEMPOL) and its analogs combine several important features, including recycleability, electron acceptance from respiratory complexes, superoxide dismutase mimicry, and radical scavenging. Although successful in antioxidant protection, their effective concentrations are too high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…Recently, we reported that mitochondria targeted electron scavengers -hemigramicidin S conjugated nitroxides -prevented both superoxide accumulation and CL peroxidation and apoptosis initiated by ActD or irradiation without affecting Bax translocation [27,28]. Combined with the results of this work showing that Bax/Bak translocation precedes superoxide production and CL peroxidation and that genetic ablation of Bax/Bak inhibited ActD and rotenone induced CL oxidation and apoptosis, we speculate that CL peroxidation not only correlates but is likely causatively and time-dependently related to mitochondrial relocation of Bax/Bak.…”
Section: Recombinant Bax Increases Mitochondrial Peroxidase Activitymentioning
confidence: 99%
“…Recently, we reported that mitochondria targeted electron scavengers -hemigramicidin S conjugated nitroxides -prevented both superoxide accumulation and CL peroxidation and apoptosis initiated by ActD or irradiation without affecting Bax translocation [27,28]. Combined with the results of this work showing that Bax/Bak translocation precedes superoxide production and CL peroxidation and that genetic ablation of Bax/Bak inhibited ActD and rotenone induced CL oxidation and apoptosis, we speculate that CL peroxidation not only correlates but is likely causatively and time-dependently related to mitochondrial relocation of Bax/Bak.…”
Section: Recombinant Bax Increases Mitochondrial Peroxidase Activitymentioning
confidence: 99%
“…The activity is presumably due to the nitroxide being reduced by ubiquinol within respiring mitochondria (90,318,319). Jiang et al (163) proposed peptidyl nitroxide conjugates for targeting mitochondria. With anticipated higher efficacy, smaller amounts of nitroxide would be required.…”
Section: The Protective Effects Of Nitroxides In Vitro and In Vivomentioning
confidence: 99%
“…Although found to be effective, the required high millimolar concentrations, partially because of its poor partitioning into cells and mitochondria, set a limit for broader applications of TEM-POL (30). Recent developments in targeted delivery of antioxidants, including nitroxides, to mitochondria offer new opportunities in radioprotection of cells and tissues (31,32). We showed that conjugation of 4-amino-2,2,6,6-tetramethylpiperidine-N-oxyl (4-AT) with a segment of gramicidin S (GS) dramatically increased intracellular and mitochondrial accumulation of the nitroxide conjugates, resulting in decreased levels of mitochondrial superoxide, inhibition of CL peroxidation, and protection of mouse embryonic cells against actinomycin D-induced apoptosis (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in targeted delivery of antioxidants, including nitroxides, to mitochondria offer new opportunities in radioprotection of cells and tissues (31,32). We showed that conjugation of 4-amino-2,2,6,6-tetramethylpiperidine-N-oxyl (4-AT) with a segment of gramicidin S (GS) dramatically increased intracellular and mitochondrial accumulation of the nitroxide conjugates, resulting in decreased levels of mitochondrial superoxide, inhibition of CL peroxidation, and protection of mouse embryonic cells against actinomycin D-induced apoptosis (31,32). Therefore, we hypothesized that mitochondria-targeted hemigramicidin S conjugated 4-amino-2,2,6,6-tetramethylpiperidine-N-oxyl hemi-GS-TEMPO may be effective in protecting cells against IR-induced cell death, thus offering a convenient therapeutic window for radiomitigation.…”
Section: Introductionmentioning
confidence: 99%